Detection and discrimination of microorganisms using Locked Nucleic Acid - Fluorescence In Situ Hybridization (LNA-FISH) - Azevedo, A. S. (2014)
The impact of multispecies biofilms on catheter-associated urinary tract infections outcome is still unclear due to the lack of adequate methodologies to discriminate the populations in situ. Employing fluorescence in situ hybridization (FISH) to discriminate the populations in a biofilm, can contribute to the understanding of microorganisms interactions in this structures. Consequently, this information might help to develop efficient strategies to prevent this disease. This work presents the first study that apply the FISH methodology using a set of LNA and/2’-O-Methyl RNA oligonucleotide probes, for the in situ detection of microorganisms in biofilms formed under conditions similar to the catheter-associated urinary tract infections.